Adaptation of Contract Models of Oil and Gas : A Comparative Study - Cut Asmaul Husna; Lina Hastuti; Iman Prihandono (Fakultas Hukum Universitas Hang Tuah, 2017)
Differences in law systems, constitution, legislation, and regimes in oil and gas business across the world enforce to have a comparative study by extending laws in oil and gas. It is, from global perspective, implemented a constant demand to the law to take essentialization categories as its base. Nature required universalism, an analysis of valid and constant law sifted toward cosmopolitan law. Manifestation of globalization was transformed and corresponded to natural regulations in adapting a contract model. Oil and gas and its exploring development within global law systems included Civil Law, Common Law, Socialist Law, Scandinavia Law, and Islamic Law. Important discoveries in oil and gas sector, therefore, might have changes by universally global cosmopolitan law.